Aquaculture Perspective of Multi-Use Sites in the Open Ocean 2017
DOI: 10.1007/978-3-319-51159-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Site-Selection and Marine Spatial Planning: The Roles of GIS-Based Tools and Models

Abstract: Around the globe, increasing human activities in coastal and offshore waters have created complex conflicts between different sectors competing for space and between the use and conservation of ocean resources. Like other users, aquaculture proponents evaluate potential offshore sites based primarily on their biological suitability, technical feasibility, and cost considerations. Recently, Marine Spatial Planning (MSP) has been promoted as an approach for achieving more ecosystem-based marine management, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…The effects associated with the wave height, that define the agitation, depending on physiographic and climatic features of the coast as well as the urban occupation of coastal areas. It compellingly leads to a good planning and maritime spatial planning, focusing on the interaction that occurs along the coast and between the sea and coastal structures, to safeguard the safety and comfort of the population (Vivero et al, 2009;Calado et al, 2010;DGPM, 2011;Becker-Weinberg, 2015;Stelzenmüller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The effects associated with the wave height, that define the agitation, depending on physiographic and climatic features of the coast as well as the urban occupation of coastal areas. It compellingly leads to a good planning and maritime spatial planning, focusing on the interaction that occurs along the coast and between the sea and coastal structures, to safeguard the safety and comfort of the population (Vivero et al, 2009;Calado et al, 2010;DGPM, 2011;Becker-Weinberg, 2015;Stelzenmüller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…None of these authors conducted studies in which all affected groups (government, experts, and users) were involved in the strategy selection, and none of them gave a solution for the spatial plan design for the development of anchorage capacities with the approach of DSC as a proven high quality "tool" for decision-makers dealing with this issue. Oz et al [38] in their study, introduced novel performance metrics aimed at measuring safety in anchorage planning, and proposed a multiobjective optimization strategy in order to maximize the utilization of the anchorage area and to minimize the risk of accidents at the same time, using a strategy called MOAP (Multi-Objective Anchorage Planner). The differences from this study are that it did not use DSC in combination with multicriteria DM and multicriteria methods that will provide support to the spatial planning specialists in designing spatial plans that are related to anchorage capacities development, using aspects of sociological, technical-economic, and the protection of natural and cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…This can be coped with the fact that most countries have just started to apply MSP. The application of DS in MSP has been found in papers dealing with the protection of environment, ecology, biodiversity, coastal, and seabed habitat features [19][20][21][22][23][24][25][26], marine traffic [27][28][29][30][31][32][33][34][35][36], anchorage planning strategy [37], and site identification (selection) [38][39][40]. It can be concluded that most of the papers, in which DSS is used in the planning of various activities in MSP, are based on ecological issues, and on the issue of regulating traffic within maritime industrial ports, but not with the development of spatial plans, and especially not with plans related to the construction of anchorages as a civil engineering problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study aimed to contribute to overcoming this particular challenge in support of ongoing efforts in developing the marine spatial plan for the Skagerrak/Kattegat. This was done by determining factors of importance for site suitability, and integrating them by means Geographic Information Systems based Multi-Criteria Decision Analysis (GIS-MCDA), a convenient tool that can provide structured and perceptible analysis about complex spatial problems (Wood and Dragicevic 2007), and is already well established as a method for aquaculture site selection (Ross, Mendoza, and Beveridge 1993;Arnold et al 2000;P erez, Telfer, and Ross 2005;Longdill, Healy, and Black 2008;Radiarta, Saitoh, and Miyazono 2008;Silva et al 2011;Micael et al 2015;Stelzenm€ uller et al 2017), though only a few studies have applied them to inform site selection specifically for macroalgae cultivation (Radiarta, Saitoh, and Yasui 2011;Sousa, Moura, and Marinho-Soriano 2012;Capuzzo et al 2014). Two alternative GIS-MCDA methods were employed and compared in this study: weighted linear combination (WLC) and the related Boolean overlay.…”
Section: Site Suitabilitymentioning
confidence: 99%